The effects of vitamin D supplementation on postoperative atrial fibrillation after coronary artery bypass grafting in patients with vitamin D deficiency. Issue 7 (26th April 2022) - Talasaz, Azita H.; Salehiomran, Abbas; Heidary, Zinat; Gholami, Kheirollah; Aryannejad, Hamid; Jalali, Arash; Daei, Maryam
Abstract: Introduction: Postoperative atrial fibrillation (POAF) as a common complication of coronary artery bypass grafting (CABG) surgery is associated with increased mortality and morbidity rates. Vitamin D deficiency increases the prevalence of POAF; however, the effects of vitamin D supplementation on the incidence of POAF have not yet been completely elucidated. Methods: In this prospective, open‐label, randomized clinical trial the level of 25‐hydroxy vitamin D (25(OH) D) was measured in patients undergoing CABG surgery. Patients with vitamin D insufficiency (defined as 25(OH) D level < 30 ng/ml) were included and randomly assigned to control group to receive either the general standard of care (Group A) or to study group to receive the general standard of care plus oral vitamin D3, 600, 000 IU 5 days before surgery (Group B). The primary outcome of our study was the occurrence of POAF during the first 5 days after CABG surgery. Results: Totally, 93 patients in group B and 103 patients in group A completed the study. The occurrence of POAF was significantly lower in group B as compared to group A (9.68% vs. 20.39%, p = .038). The length of intensive care unit (ICU) stay and hospital stay were reduced in group B patients (2.21 vs. 3.86 days, p < .001 and 7.40 vs. 9.58 days, p = .022, respectively). Conclusion: Our study demonstrated that vitamin D supplementation reduces the incidence of POAF, duration of ICU, and hospital stay following CABG surgery.